2009
DOI: 10.1056/nejmoa0909938
|View full text |Cite|
|
Sign up to set email alerts
|

Advanced Heart Failure Treated with Continuous-Flow Left Ventricular Assist Device

Abstract: Treatment with a continuous-flow left ventricular assist device in patients with advanced heart failure significantly improved the probability of survival free from stroke and device failure at 2 years as compared with a pulsatile device. Both devices significantly improved the quality of life and functional capacity. (ClinicalTrials.gov number, NCT00121485.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
1,858
7
25

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,778 publications
(1,965 citation statements)
references
References 22 publications
36
1,858
7
25
Order By: Relevance
“…Survival, transplantation rates, and hospitalizations were similar during follow‐up. Mortality rates noted in our study are comparable to randomized trials of CF‐LVAD as well as prior studies evaluating ICD therapies in LVADs 1, 2, 6, 19, 20…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Survival, transplantation rates, and hospitalizations were similar during follow‐up. Mortality rates noted in our study are comparable to randomized trials of CF‐LVAD as well as prior studies evaluating ICD therapies in LVADs 1, 2, 6, 19, 20…”
Section: Discussionsupporting
confidence: 87%
“…VAs are commonly seen following LVAD implantation, with the incidence ranging from 24% to 52% 2, 13, 21, 22. Multiple mechanisms contribute but delayed incidence of VAs is mostly secondary to pre‐existing substrate combined with a lack of favorable remodeling from the LVADs 23, 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that published data showed that the initial device strategy did not necessarily correspond to the final use of the device; BTT and DT are unlikely to be mutually exclusive categories 25, 28, 29. For example, in the randomized controlled trial of LVAD (continuous‐flow device vs. pulsatile‐flow device), 13% of DT patients received a donor heart within 2 years after implantation 30. On the other hand, less than 50% of BTT patients had received a donor heart 2 years after LVAD implantation 31.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous‐flow LV assist devices (LVADs) are becoming the standard of care for management of refractory advanced heart failure patients 14, 15, 16, 17. Although implantation of an LVAD leads to mechanical unloading of the LV, may induce ventricular reverse remodeling, and generally improves TR in the short term,18, 19, 20 nonimprovement of significant preoperative TR or TR worsening (namely “residual TR”) is observed in some patients during mid‐ to long‐term LVAD support.…”
Section: Introductionmentioning
confidence: 99%